Pemanfaatan Platform Gamifikasi (Quizizz/Kahoot) sebagai Inovasi Formatif Assessment Interaktif - A. Nurul Muta’ali; Suci Wahyuni; Selvianti; Risma Handayani (Al-Kindi, 2026)
Gamification platforms such as Quizizz and Kahoot have become significant innovations in modern education. This study aims to analyze the effectiveness of using gamification platforms in formative assessment as an innovative alternative to traditional learning evaluation methods. Formative assessment is a continuous assessment process designed to provide feedback to students and teachers to improve the quality of learning. This study involved 120 students from three secondary schools with a quasi-experimental research design (pretest-posttest control group design). Data were collected through formative tests, student perception questionnaires, learning observations, and analysis of student engagement in the platforms. The results showed that the use of the Quizizz and Kahoot platforms significantly increased student engagement levels by 78% compared to the control group, increased material comprehension by 23%, and created a more interactive and enjoyable learning environment. Furthermore, these platforms facilitated real-time data collection that helped teachers identify learning gaps more quickly and accurately. The research findings imply that integrating gamification platforms into formative assessment practices can be an effective solution to improve the quality of learning evaluation and student learning motivation in the digital era.